Prevalence of Foodborne Pathogens in Pacific Northwest Beef Feedlot Cattle Fed Two Different Direct-Fed Microbials - Makenzie G. Flach; Onay B. Dogan; Wanda M. Kreikemeier; Kendra K. Nightingale; Mindy M. Brashears (Journal of Food Protection, 2023)
In recent years, there has been an increased interest in beef cattle shedding of foodborne pathogens due to the potential to contaminate surrounding food crops; however, the number of studies published on this topic has declined as the majority of research has emphasized on postharvest mitigation efforts. A field study was conducted to determine the prevalence of pathogens and indicator bacteria in beef cattle fed two different direct-fed microbials (DFMs). Fecal samples from a total of 3,708 crossbred yearling cattle randomly assigned to 16 pens and two treatment groups at a commercial cattle feedlot were taken. During the study period, diets were supplemented with two different DFMs i.) Lactobacillus acidophilus (NP51) and Propionibacterium freudenreichii (NP24) (9 log10CFU/head/day), and ii.) Lactobacillus salivarius (L28) (6 log10CFU/head/day). Fecal samples from pen floors were collected on days 0, 21, 42, 63, 103, and analyzed for the presence of Salmonella and E. coli O157:H7 and concentration of E. coli O157:H7, Enterobacteriaceae, and C. perfringens. Fecal samples collected from cattle fed L28 had significantly lower concentration of C. perfringens (p < 0.05) and had a similar prevalence with no significant differences in E. coli O157:H7 as those fed NP51/NP24 through the study until day 103. On day 103, the prevalence in cattle fed L28 was 40% with a concentration of 0.95 log10MPN/g while those fed NP51/NP24 were 65% with a concentration of 1.2 log10MPN/g. Cattle supplemented with NP51/NP24 achieved a significant log reduction of EB by 2.4 log10CFU/g over the course of the 103-day supplementation period compared to L28. Salmonella prevalence was also measured, but not detected in any samples at significant amounts to draw conclusions. It is evident that E. coli O157:H7 and other foodborne pathogens are still prevalent in cattle operations and that preharvest mitigation strategies should be considered to reduce the risk to beef products.